Outdoor Games in The System of Physical Culture and Sports in Higher Education - Madaminov Oribjon Nishanbayevich (Zien Journals, 2022)
This article talks about the playful form of physical education classes in higher educational institutions, which contributes to the formation of educational motivation for physical education in general for all students, and in combination with other educational means is the basis for the formation of a harmoniously developed, active personality combining physical development and physical perfection
Keywords: Physical education; students; outdoor games; motivation